THE EFFECT OF PROFITABILITY, GROWTH OPPORTUNITY, ASSET STRUCTURE AND LIQUIDITY ON CAPITAL STRUCTURE - Anggi Elisabeth Bate'e; Hottua Samosir; Wisnu Rayhan Adhtya (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The purpose of this study was to examine the effect of profitability, growth opportunity, asset structure and liquidity on the capital structure of companies in the consumer industry sector listed on the Indonesia Stock Exchange. 2018-2021 years. The analytical method used in this research is multiple linear regression with SPSS. Observations in this study used purposive sampling and obtained a sample of 34 companies by testing the classical assumptions, multiple linear regression, hypothesis testing and the coefficient of determination. The conclusions from the results of this study indicate that partially profitability, asset structure and liquidity have a significant effect on capital structure while growth opportunities do not have a significant effect on capital structure. Simultaneously the four factors namely profitability, growth opportunity, asset structure and liquidity have a significant influence on capital structure